2017
DOI: 10.14297/jpaap.v5i2.276
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Student Transition into Professional Practice

Abstract: Transitions can affect students throughout their time at university. This study aims to show the potential of an additional, non-assessed placement in supporting MA3 Initial Teacher Education (ITE) students with skills thought to benefit transitions. Much of the research around student transitions focuses upon transitions into and out of higher education. In addition, within the MA ITE programme, students perceive challenges in transitioning into Professional Practice during their four year programme. A pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This stress impacts on the experience for the students and is a concern to them before, during and after the placement. Interestingly, preliminary research by Dey, Lindsay and Thomson (2017) found that students who completed placement experience without summative assessment attached did not feel this pressure, instead embracing the opportunity to develop skills before a placement with assessment. Within University B, there are 40 credits associated to this module, which may account for why this cohort felt more strongly than University A (where there are only 20 credits associated to the module).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This stress impacts on the experience for the students and is a concern to them before, during and after the placement. Interestingly, preliminary research by Dey, Lindsay and Thomson (2017) found that students who completed placement experience without summative assessment attached did not feel this pressure, instead embracing the opportunity to develop skills before a placement with assessment. Within University B, there are 40 credits associated to this module, which may account for why this cohort felt more strongly than University A (where there are only 20 credits associated to the module).…”
Section: Discussionmentioning
confidence: 99%
“…However, shorter placements can also be a positive learning experience for students (Knight and Yorke, 2004). Research by Dey, Lindsay and Thomson (2017) concluded that students who completed a short placement (eight afternoons) within the early years found the experience useful in developing skills. Related to this, the placement experiences from both universities in this study are deemed 'short' placements.…”
Section: The Context Of Placement Experiences In Undergraduate Programmesmentioning
confidence: 99%
See 1 more Smart Citation